The Politics of Inclusive Development: Interrogating the Evidence - Sam Hickey; Kunal Sen; Badru Bukenya (Oxford University Press, 2015)
This collection brings together internationally-renowned experts to offer a comprehensive review of how politics shapes inclusive development in the global south. Each aspect of development is covered: social, economic, environmental and cultural, with each substantive chapter offering a systematic review of the evidence in the relevant field.
Keywords: 330; politics; inclusive development; political settlement; accumulation; citizenship; recognition; transnational